High T2-weighted signal intensity is associated with elevated troponin T in hypertrophic cardiomyopathy. Issue 4 (9th August 2016) - Gommans, DH Frank; Cramer, G Etienne; Bakker, Jeannette; Michels, Michelle; Dieker, Hendrik-Jan; Timmermans, Janneke; Fouraux, Michael A; Marcelis, Carlo LM; Verheugt, Freek WA; Brouwer, Marc A; Kofflard, Marcel JM
Abstract : Objective: Areas of high signal intensity (HighT2) on T2-weighted cardiovascular magnetic resonance (CMR) imaging have been demonstrated in hypertrophic cardiomyopathy (HCM). It has been hypothesised that HighT2 may indicate active tissue injury in HCM. In this context, we studied HighT2 in relation to cardiac troponin. Methods: Outpatient HCM patients without a history of coronary artery disease underwent CMR imaging at 1.5 T using T2-weighted, cine and late gadolinium enhancement (LGE) imaging to assess HighT2, left ventricular (LV) function, LV mass and the presence and extent of LGE. Highly sensitive cardiac troponin T (hs-cTnT) was assessed as a marker of injury, with hs-cTnT ≥14 and >3 ng/L defined as an elevated and detectable troponin. Results: HighT2 was present in 28% of patients (28/101). An elevated hs-cTnT was present in 54% of patients with HighT2 (15/28) compared with 14% of patients without HighT2 (10/73) (p<0.001). Hs-cTnT was detectable in 96% of patients with HighT2 (27/28) compared with 66% of patients without HighT2 (48/73) (p=0.002). In case of an undetectable hs-cTnT, HighT2 was only seen in 4% (1/26). In addition, the extent of HighT2 was related with increasing hs-cTnT concentrations (Spearman's ρ: 0.42, p<0.001). Conclusions: In this CMR study of patients with HCM, we observed HighT2 in a quarter of patients, and demonstrated that HighT2 was associated with an elevated hs-cTnT. This observation, combined with the very high negative predictive value of an undetectable hs-cTnT for HighT2, provides supportive evidence for the hypothesis that HighT2 is indicative of recently sustained myocyte injury.